(untitled) - Teague, Michael (New York, 2013)
It’s not just Personal! Your Health Today teaches Personal Health from a truly inclusive and socially responsible perspective. While each of us has a unique set of individual characteristics that shape our health, other environmental factors have an impact on our well being too. Your Health Today incorporates the individual, interpersonal, and broader social factors that affect our health, acting as a guide for healthy living in college and beyond. Students will complete a guided Personal Health portfolio online, applying concepts they learn from the text to their own lives in assessments that give automatic feedback. In doing so, students are able to see how their own family history, community, and culture affect their personal health decisions.
Keywords: Health promotion,Giáo dục sức khoẻ,Cải tiến sức khoẻ,Health education